Acne Vulgaris in Saudi Arabia - Myths and Common Misconceptions: A Cross-sectional Study - Manal A. Aldosari; Dalal A. Aldosari; Rahaf H. Almutairi; Turki A. Aldosari; Asem M. Shadid; Fajer M. Alzamil (Wolters Kluwer Medknow Publications, 2024)
Background: Acne vulgaris is a long-term condition of the sebaceous glands that usually occurs during puberty. The mean prevalence of acne in Saudi males is 54% and ranges from 54% to 84% among Saudi females. Despite the high prevalence of acne vulgaris, it is shrouded in multiple misconceptions that are widely spread among the general public and among patients with acne. Purpose: This study is conducted to assess the knowledge, awareness, and widespread myths and misconceptions about acne vulgaris. Methods: A cross-sectional quantitative study was conducted in Saudi Arabia in August 2022 through 1164 self-administered, convenient sampling technique online questionnaires. Sociodemographic data, as well as knowledge regarding acne and its treatment, were collected and evaluated. Results: Three-quarters of the respondents (73%) knew that stress precipitated acne, and two-thirds (66%) knew that fat-rich food could increase the risk of developing acne. Knowledge was lower in males than females, while a family history of acne was associated with higher knowledge. Most respondents (76%) knew that hormonal changes could precipitate acne. More than half of the respondents did not know whether Vitamin A derivatives increased the risk of depression (61%), anxiety, and stress (55%). Three-quarters of the respondents (73%) knew that stress precipitated acne, and two-thirds (66%) knew that fat-rich food could increase the risk of developing acne. The most common source of information was the Internet (40.8%) followed by social media platforms (25.2%) and physicians (15.2%). Conclusion: There was an adequate level of knowledge. Approximately half of the respondents declared the Internet as a source of their information. We recommend physicians to educate their patients about acne, to elaborate society-oriented campaigns, and to encourage dermatologists to spread information through the Internet and social media platforms as they are considered a major source of information in this study.